TIMELINE OF PUBLIC POLICIES FOCUSED ON EDUCATIONAL COMPUTING - Falcade, Lais (2024)
Over the past fifty years, computer science has been gradually integrated into the Brazilian education system. This integration has gone through several phases and programs, each with its own goals and challenges. Since Decree No. 84,067 in 1979, which established the National Computer Science Policy, to the creation of ProInfo in 1997 and the Connected Education Innovation Policy (PIEC) in 2023, there has been significant progress, but also difficulties in the effective implementation of these policies. This study seeks to understand public policies aimed at computer science in a historical context, exploring their evolution within the scope of Brazilian education, and highlighting initiatives and programs that shaped the insertion of digital technologies in teaching. To construct this article, a qualitative approach was adopted, with bibliographical research. With this history, it was possible to build an interactive timeline that presents the public policies designed in Brazil for the computerization of schools and teacher training, culminating in the teaching of computer science, currently proposed for Brazilian basic education schools, in the National Common Curricular Base and its Complement.